Lucky breaks [compact disc, unabridged] - Patron, Susan, 1948- (Random House/Listening Library, 2009)
Lucky makes a new friend, gets stuck in a well, meets up with a wild burro, discards something she didn't know was precious, and discovers the secret of the universe in this charming and funny sequel to the Newbery Award-winning The higher power of lucky.